Hindustani Music and Science in Thirteenth Century BC: A Study of Pt. Sharangdev's 'Sangeet Ratnakar': Exploring the scientific aspect of Hindustani music through the analysis of Pt. Sharangdev's 'Sangeet Ratnakar' (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Studies in the scientific aspect of Music are very less and which are available have studied Music through modern scientific inspection through the science of sound. The study through the science of sound which mainly developed in the west causes the non-inclusion of oriental studies especially those in the native languages. The modern studies in Hindustani Classical Music lack the orientation towards Musical Treaties which contains large data on Music. The treaties and Granthas on Hindustani Classical Music which were written in time explain the details of their contemporary music to a minute level in the form of Sanskrit shlokas. The neglecting of these treaties can lead to their disappearance and further the inclination of musical studies towards modern scientific approach. The study is comprised of the analysis of Grantha ‘Sangeet Ratnakar’ to find out the shlokas quoting the scientific aspect of music and the properties of sound (pitch, intensity and timbre). Through this study it is found that, Sangeet Ratnakar describes the music of its time through the properties of sound. Although the terminology is different but the concepts used are scientific.